The Relation of Occupational Identity, and Family Background Variables in a Hungarian Sample of Emerging Adults - A. Elekes, Szende (European Journal of Mental Health, 2019)
Method: Besides demographic variables and data regarding the participants’ family background, we used the Melgosa Occupational Identity Scale (OIS), Parental Authority Questionnaire (PAQ). The sample consisted of 220 19–29-year-old emerging adults. Background: In the last few decades, identity formation has been postponed until the mid or late twenties (ARNETT 2000). ARNETT calls this specific period between 19–27 emerging adulthood. According to WATERMAN (1999), some family variables can foster or hinder the process of identity development. In our study, we investigate the relation of parenting styles described by BAUMRIND (1991), two-parent or one-parent family backgrounds, and occupational identity. Among the dimensions of identity, we will focus on occupational identity, since it has great importance in this period of life. Results: According to our hypothesis, identity diffusion and moratorium show a slightly negative correlation with age. Regarding occupational identity, it seems significant whether the person could or could not find a job in accordance with their qualifications: the moratorium is higher among those who could not, while foreclosure and identity achievement is higher among those who found a job in their professional field. Regarding family background, it seems that children of divorced parents do now show higher rates of less adaptive identity statuses, but foreclosure is higher among children raised in two-parent families. Conforming to our expectations, we found that permissive parenting is related to identity diffusion, while interestingly, both the father’s and the mother’s authoritative parenting is related to foreclosure.